Axial compressive performance of seawater sea sand concrete-filled CFRP-stainless steel tube short columns. (10th March 2023) - Chen, Zongping; Qin, Weiheng; Liang, Yuhan; Zhou, Ji
Highlights: A reinforcement method of CFRP pasting the internal wall of stainless steel tube to confine seawater sea sand concrete is adopted. With the same CFRP layers, the effects of CFRP pasting methods on the mechanical properties of specimens are compared. With the same CFRP pasting methods, the effects of the number of CFRP layers on the mechanical properties of specimens are analyzed. The strain-hardening effect of stainless steel is considered and a bearing capacity calculation formula of SCSST columns based on the limit equilibrium method is proposed. Abstract: In order to improve the bearing capacity and durability of thin-walled stainless steel structures, the internal and external walls of stainless steel tube were pasted with CFRP to form CFRP-stainless steel composite tube, and the axial compressive mechanical properties of seawater sea sand concrete-filled carbon fiber-reinforced polymer (CFRP)-stainless steel tube (SCSST) short columns were investigated in this study. Twenty-one specimens were tested with the CFRP pasting methods and the number of CFRP pasting layers as the variation parameters. The results indicate that the failure modes of the specimens without CFRP and internal CFRP specimens were shear damage, while the external CFRP specimens were waist drum damage, all CFRP were fractured. CFRP and stainless steel tube had good cooperative performance. The bearing capacity, damage and energy absorption suppression of specimens were improved with the increase of CFRP layers, but the ductility and initial stiffness increased first and then decreased. With the same layers of CFRP, the mechanical properties of internal CFRP specimens were better than those of external CFRP specimens, and the ultimate bearing capacity could be increased by 5.5% and 8.8%. Finally, the strain-hardening effect of stainless steel was considered and a bearing capacity calculation formula of SCSST short columns based on the limit balance method was proposed, and 115 data samples were collected to verify the calculation formula.